Low Dose β Carotene Supplementation Diminishes Oxidative Stress in Type 2 Diabetics and Healthy Individuals - José M. Moreno; Irene Leets; Rafael J. Puche; Ana M. Salazar; Jham F. Papale; Gloria Alvarado; María N. García-Casal (Journal of Pharmacy and Nutrition Sciences, 2013)
Type 2 diabetes is a chronic, multifactorial disease, and oxidative stress one of the pathophysiological mechanisms associated with its appearance and development. The objective was to determine the effect of supplementation with β-carotene to type 2 diabetics and healthy individuals, on iron metabolism, oxidative balance, and antioxidant plasma capacity, using doses similar to the daily nutritional requirement. A total of 117 randomly selected non-smoker volunteers participated in the study. Type 2 diabetics (34) and healthy individuals (24), received 6 mg β-carotene for 45 d, and were compared to similar non-supplemented diabetic (33) and control (26) groups. Blood samples were taken at the beginning, end and 30 days after finishing supplementation, to determine hemoglobin, hematocrit unsaturated iron binding capacity, total iron binding capacity, transferrin saturation, ferritin, glycemia, glycosilated hemoglobin, cholesterol, triglycerides, HDL, LDL, oxidized LDL, copper, zinc, TBARS, FRAP, nitrites, GPx, SOD, folates, retinol and β-carotene. In supplemented diabetics, there was a significant diminution in copper concentrations (24.8%), and TBARS (9.5%), associated with a non significant increase in FRAP. Also, hemoglobin decreased and oxidized LDL augmented in supplemented diabetics. All the changes were still present one month after finishing the supplementation. In conclusion, supplementation with β-carotene had a positive effect on the oxidative balance of both, type 2 diabetics and healthy individuals, which makes the inclusion of β-carotene rich foods, part of the prevention and/or treatment strategies in type 2 diabetes.